The challenges of teaching and learning Arabic in China - Hao, J.J.; Ismail, Z. (2011)
The main purpose of this study is to elaborate the Arabic language teaching and learning in China. Arabic is a common language of Arab nation and one of the working languages of the United Nation. At the same time, it is the language of the Holy Quran, a main scripture of Islam. Arabic language propagated into China with Islam since Tang Dynasty in 651 years. At beginning with the basic purpose of communication the Chinese people start to learning Arabic language from the Arabic people. With the Arabic language's political statue / start more and more important, there are more and more Chinese people start to study Arabic. At the same time, one form of education was founded Mosque Education. Since the first Arabic school was founded until now through thousands years development of Arabic teaching, nowadays there are three formal styles of Arabic teaching - University, Islamic College there and Military University. Except these three styles of Arabic teaching, there is another style of Arabic teaching is personal Arabic school. Through thousands years development until now Chinese Arabic teaching had great development and face to a great challenge.